The effects of traffic light labels and involvement on consumer choices for food and financial products. (14th March 2014) - Drescher, Larissa S.; Roosen, Jutta; Marette, Stéphan
Abstract Traffic light (TL) labels that inform consumers regarding product safety have received increasing attention in different fields. Behind the background of behavioural economics, this paper presents the results of a split‐sample choice experiment conducted in Germany to evaluate the impact of TL labelling on purchases of food and financial products. We hypothesize that consumers experience different levels of involvement with these two types of products, leading to different recommendations regarding the use of TLs. The results show that TLs affect consumer purchases of both product groups by focusing their attention on specific product attributes. For food, whereas the low‐fat attribute has no significant impact on food choices that do not include TLs, this attribute has a positive impact on choices once it is signalled with a TL label. The positive evaluation of the organic production attribute of a food product without a TL decreases when the same product is labelled with a TL. In the case of financial products, TLs significantly reinforce the impact of all characteristics on choice probability. TLs also generate a halo effect with regard to return variance. Although consumers demonstrate different levels of involvement for the two types of products, involvement does not always impact the evaluation of attributes. Compared with less involved consumers, more involved consumers exhibit more heterogeneous evaluations of the return variability attribute in the case of the financial product and the organic attribute in the case of the food product.